Report of a rare case: supernumerary tooth between the roots of the permanent maxillary first molar: Opis redkega primera: Nadštevilen zob med koreninami prvega zgornjega stalnega kočnika - Strmšek, Lucija; Štamfelj, Iztok (Acta Medico-Biotechnica, 2022)
Purpose: To present the case of a patient with an inter-radicular supernumerary tooth.Case report: A 45–year–old male patient presented with sepsis of odontogenic origin. Oral clinical investigation and panoramic radiography revealed the presence of four avital teeth with inadequate root canal fillings, including both maxillary first molars. The right one had periapical radiolucencies, indicating periapical periodontitis. The left one had an unusual radiopaque structure between the roots. Condensing osteitis, odontoma, and benign cementoblastomawere included in differential diagnosis; however, cone-beam computed tomography (CBCT) showed a miniature supernumerary tooth located between the buccal roots of this tooth. Surgical removal of the inter-radicular tooth was not indicated, because there were no associated pathological changes. Subsequently, the right first molar was extracted as the most likely source of systemic infection. The remaining three avital teeth were endodonticallyre-treated.Conclusion: An inter–radicular supernumerary tooth is a rare occurrence; however, it is important to take into account when evaluating a radiopacity associated with a permanent maxillary molar. Its image on conventional radiographs may be unclear due to overlap with the neighbouring roots. CBCT plays a leading role in radiologic diagnosis and the establishment of  anatomical relationships.
Keywords: tooth abnormalities, hyperodontia, dental radiography, differential diagnosis